MEMAHAMI HAKIKAT PEMBELAJARAN PKN SEBAGAI PENDIDIKAN KARAKTER DI SEKOLAH DASAR - arisandhi, Pipit; Sanjaya, Dewa Bagus; Suastika, I Nengah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Civics Education (PKn) at the elementary school level plays a strategic role in shaping the character and identity of the nation. As a multidimensional subject, PKn not only teaches legal and political aspects but also instills moral values, democracy, and nationalism based on the principles of Pancasila. This article explores the essence of PKn at the elementary level, the instructional principles applied, and its urgency in developing students' character from an early age. PKn instruction emphasizes active, cooperative, participatory, and reactive learning approaches aimed at fostering intelligent, responsible, and morally upright citizens. In the context of national character building, PKn serves as a vital medium for internalizing national values and social ethics amidst the challenges of moral decline among the younger generation. The article recommends that PKn teachers fulfill their roles optimally through comprehensive and collaborative approaches, while cultivating a school culture that supports positive character formation. Thus, PKn becomes a foundational pillar in preparing future generations who are patriotic and embody the values of Pancasila.